ANALISIS GAYA BAHASA PERBANDINGAN DALAM HIKAYAT IBRAHIM HASAN KARYA NURMAN SYAMHAS - Dinda Deswita; Mohd. Harun; Subhayni Subhayni (JIM Pendididikan Bahasa dan Sastra Indonesia, 2022)
ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan jenis-jenis gaya bahasa perbandingan yang terdapat di dalam hikayat Ibrahim Hasan karya Nurman Syamhas  dan mendeskripsikan gaya bahasa perbandingan  yang paling dominan muncul di dalam hikayat Ibrahim Hasan karya Nurman Syamhas. Sumber data dalam penelitian ini adalah hikayat Ibrahim Hasan karya Nurman Syamhas. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Pengumpulan data dilakukan dengan teknik dokumentasi. Hasil analisis yang telah didapatkan dalam hikayat Ibrahim Hasan karya Nurman Syamhas dalam gaya bahasa perbandingan,yaitujenis gaya bahasa perbandingan yang berbentuk metafora, ironi, antonomasia, alegori, parabel, fabel, personifikasi. Gaya bahasa perbandingan yang paling dominan muncul dalam hikayat tersebut adalah gaya bahasa metafora.Kata kunci: hikayat, gaya bahasa perbandingan, ibrahim hasan. ABSTRACT The study is entitled "Comparative Language Style in the saga of Ibrahim Hasan by Nurman Syamhas". The formulation of this research problem is (1) what kind of comparative language style is contained in the story of Ibrahim Hasan by Nurman Syamhas? and (2) what is the most dominant language style in the story of Ibrahim Hasan by Nurman Syamhas? The aims of this study are (1) to describe the types of comparative language styles contained in the Ibrahim Hasan saga by Nurman Syamhas and (2) to describe the most dominant type of comparative language in the story of Ibrahim Hasan by Nurman  Syamhas. The method used in this research is qualitative descriptive method. The result of analysis that has been obtained in the story of Ibrahim Hasan by Nurman  Syamhas of comparative language style,. Types of comparative language styles and the number of types of comparative language styles are, metaphorical, irony, antonomasia, allegory, parables, fable, and personification. The most dominant language style comparison that appears in the saga is the style of the metaphorical language.Keywords: comparative language style, saga, ibrahim hasan.